2018
DOI: 10.1002/cctc.201702053
|View full text |Cite
|
Sign up to set email alerts
|

Traveling Hot Spots in Plasmonic Photocatalysis: Manipulating Interparticle Spacing for Real‐Time Control of Electron Injection

Abstract: Herein, we introduce a novel approach to achieve real‐time control over the hot‐electron injection process in metal–semiconductor photocatalysts. Such functionality is attained through the design of a hybrid nanocomposite in which plasmonic Au nanorods and TiO2 nanoparticles are synergistically integrated with a thermoresponsive polymer. In this manner, modifying the temperature of the system allows 1) precise regulation of the interparticle distance between the catalyst and the plasmonic component and 2) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Moreover, it is interesting to look at the local properties of hot-electron generation since previous works have demonstrated that the electromagnetic eld enhancement created at interparticle gaps can enhance signi cantly the generation of hot electrons at the metal-semiconductor interface. 10 Figures 3e and S8 show the calculated local properties of the R-ribbon model (this helicity is representative for both enantiomers) under directional CPL excitation in the vicinity of the plasmon resonance, with the K-vector parallel to the main axis of the helix (K||+z). Figure 3e demonstrates the generation of strong electromagnetic elds at the gaps between Au NPs only in that geometry in which the polarization of the directional excitation matches the handedness of the substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is interesting to look at the local properties of hot-electron generation since previous works have demonstrated that the electromagnetic eld enhancement created at interparticle gaps can enhance signi cantly the generation of hot electrons at the metal-semiconductor interface. 10 Figures 3e and S8 show the calculated local properties of the R-ribbon model (this helicity is representative for both enantiomers) under directional CPL excitation in the vicinity of the plasmon resonance, with the K-vector parallel to the main axis of the helix (K||+z). Figure 3e demonstrates the generation of strong electromagnetic elds at the gaps between Au NPs only in that geometry in which the polarization of the directional excitation matches the handedness of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…9 Moreover, assemblies with strong interparticle plasmonic coupling can produce an increase in the local electromagnetic eld enhancement that leads to an improved separation of charges at the interface, thus producing an enhanced photoactivation of the semiconductor. 10 Meanwhile, recent developments in colloidal chemistry have been used to create chiral plasmonic NPs, either as isolated objects or as assemblies, with chiroptical activities. [11][12][13][14] It has been postulated that the hot charges produced in these geometries can be sensitive to the polarization of circularly polarized light (CPL), 15,16 hence opening the door to a number of new photochemical applications, such as detection of chirality at the nanoscale, chiral growth of nanocrystals or asymmetric photodecomposition of plasmonic assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a “layer-by-layer” process was conducted in order to obtain a sequential adsorption of the different components [29], leading to the formation of reproducible interfaces between the plasmonic photosensitizer and the large bandgap semiconductor, while providing long term colloidal stability to the system. This approach has been previously used by us to attach plasmonic and semiconductor NPs onto colloidal substrates such as silica or poly(N-isopropylacrylamide) (pNIPAM) sub-micrometric spheres [6,10]. In both cases, the homogeneous distribution of both components and the regular interfaces created between them result in the ideal scenario to study hot electron injection mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the presence of these plasmonic hot spots at the Schottky barrier maximizes the electron injection and, ultimately, the photosensitization of the semiconductor. In a similar way, the narrow gaps created through the controlled assembly of plasmonic objects can result in a further enhancement effect [9,10]. These examples show that a rational design of the hybrid photocatalyst and hence, the specific combination of the different components, can lead to better physical interactions, with consequent improved photocatalytic capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they concluded that the absorption cross section could be increased with narrower gaps (Figure 4a), which then promoted higher rates for generating HCs (Figure 4b). Similarly, Correa-Duarte et al [70] loaded Au rods-TiO 2 on the thermo-responsive polymer and controlled such gap "hot spots" structures dynamically by shrinking or expanding this substrate, mediated by variations of the temperature (Figure 4c). In an experiment of dye decomposition, they demonstrated the improvement of the rates for degrading RhB, which resulted from "hot spots" effects, in which the temperature, when increased to 40 • C, was more effective than in the case of 25 • C (red region for 40 • C and blue region for 25 • C in Figure 4d).…”
Section: Design Of Structures With "Hot Spots"mentioning
confidence: 96%